Ovarian cancer in the elderly: feasibility of surgery and chemotherapy in 89 geriatric patients. Issue 3 (1st May 2007) - Susini, T.; Amunni, G.; Busi, E.; Villanucci, A.; Carriero, C.; Taddei, G.; Marchionni, M.; Scarselli, G.
Abstract : Gynecological oncologists are faced with an increasing proportion of geriatric ovarian cancer patients. Comorbidities are frequently a matter of concern in this age group, and what is adequate treatment for such patients is still debated. The aims of this study were to analyze the feasibility of standard surgery and chemotherapy in a series of elderly ovarian cancer patients (≥70 years) and to investigate the influence of age (70–75 vs >75 years) on survival. We retrospectively evaluated 89 elderly patients treated at our department between 1985 and 2005. Comorbidities, type of surgical procedure, complications, drugs and schedules of chemotherapy, number of cycles, toxicity, and clinical outcome were registered. Comorbidities were present in 71.9%. Only six patients were inoperable. Among the 83 patients who underwent surgery, 76.4% received adequate surgical treatment. Severe postoperative complications occurred in 16.8%, operative mortality was zero. A total of 801 cycles of chemotherapy were administered to 77 patients (median 10; range 1–38). Overall, G3–G4 toxicity was documented in 61.0%. The rates of dose reduction, treatment delay, and discontinuation were 13.0%, 20.7%, and 3.9%, respectively. Patients who received adequate surgery and those with residual disease <1 cm did significantly better than their counterparts ( P = 0.04 and P < 0.001, respectively). No difference in survival according to age (70–75 vs >75 years) was found. Standard surgery and chemotherapy were feasible in elderly ovarian cancer patients. The type of surgery and the amount of residual disease, but not the age of the patients, significantly influenced the clinical outcome.